EFEK PUBLIKASI NEGATIF TERHADAP SIKAP DAN PERILAKU KARYAWAN - Saroyeni Piartrini, Putu (PIRAMIDA; Vol. 6, No.1 Juli 2010)
Organizations spent a considerable effort and time to build positive image and organizationcommitment. This article explore whether negative information about the labor practices of anorganization and unethical conduct of part of the employee of the organization affectemployees’ attitude and behavior. Based on social identity theory and relevant research findings,this article explores the potential effects of negative publication of employees behavior ororganizational practices on employees’ attitude toward organization and their commitmenttoward organization.Organizations needs to build effective and intensive communication mechanism to build andimprove employee identification toward organization. High employee identification towardorganization will moderate the impact of negative organization publication on employee attitudeand employee commitment.
Keywords: Negative publication, organization identification, employee’s attitude, employee’s commitment.